Hiperbola pada puisi "Syair Pujian Untuk Laila" dalam novel Laila dan Majnun karya Nizami Ganjavi - Rosya Indah (TEXTURA, 2021)
This study discussed hyperbole in "Syair Pujian Untuk Laila" in Layla and Majnun's novels by Nizami Ganjavi. The use of figures of speech in poetry gives poetry a variety of meanings. Every poet has different styles of speech. One of the poets who specialized in the language style of the words was Nizami Ganjavi. Nizami Ganjavi is a Persian poet who is famous with his work entitled “Laila dan Majnun”, in that novel there are many poems and one of them is “Syair Pujian Untuk Laila”.  In "Syair Pujian Untuk Laila," the poet used a lot of hyperbole. The purpose of the study was to learn the hyperbole found in Nizami Ganjavi's "Syair Pujian Untuk Layla," and to describe the meaning of the hyperbole in the poem. The study employs descriptive qualitative methods.